Marx (1843-1852): política e revolução - um (re)encontro com a emancipação do trabalho - Serpa, Paola Baldovinotti [UNESP] (2014)
The purpose that drives this research is to apprehend, in its concepts, the political category in Marx's thought, explaining that his conception develops a path of continuity, reaffirming on his maturity the bases of the ontological rewiew he had started in his youth. Rewiew, therefore, that not only shifts the historical spot that politics has taken place so far, as well as it focus the emancipation of labor. Its precise apprehensiveness is a prerequisite for the achievement of the revolutionary struggle. In order to provide evidence that may help to elucidate the controversy of the alleged break between the theoretical production of the young Marx and scientist itself, we propose that the study be defined mainly by Marx‟s writings produced in the decade 1843-1852, incorporating both, texts of his youth as well as the materials recognized as achievements of maturity. To resume the ontological dimension of the formulations of Marx gives way to an intense ideological debate within Marxism itself, with direct implications for the delimitation of its social function in the struggle to overcome social estrangements and the consequent emancipation of individuality in the affirmation of genuine human gender. In this sense, we intend to demonstrate that, besides, to sustain the opposition that privileges the later writings in order of those produced earlier – that means, the Marx‟s epistéme – compromises the emancipatory struggle in its main point, enhancing the political form in discountenance of the realization of human freedom in the self-edification of men‟s world by social labor.